Integrated resistance management for acaricide use on Varroa destructor - Lester, Philip J. (Frontiers in Bee Science, 2023)
The global beekeeping industry faces an escalating challenge in the form of Varroa destructor. Synthetic chemicals serve as a cornerstone for varroa management, although they face a major challenge in the form of acaricide resistance. Here, I examine acaricide resistance in varroa under the framework of Insecticide Resistance Management (IRM). I assess the potential of diverse IRM strategies, such as pesticide rotation and mixtures, refuge utilization, synergists and the integration of non-persistent chemicals. The peculiar life history of varroa, characterized by its incestuous breeding system, challenges conventional IRM strategies. There is little published evidence that pesticide rotation is beneficial for resistance management in varroa, with several studies showing resistance is maintained despite rotation. Fitness costs associated with pesticide resistance are often an essential component for IRM strategies, but there are no current data from varroa demonstrating such specific fitness costs (e.g., a reduced relative oviposition rate) associated with resistance. The single published experimental study directly examining relative fitness found that here was little or no reproductive fitness cost associated with pyrethroid resistance. More work is needed on fitness effects of the key acaricides, which would better guide the use of rotation and refuge strategies. A key prospect for future work that has been identified through simulation modelling is offered by pesticide mixtures and the role of synergists to elevate acaricide efficacy. Additional tools for varroa IRM include ‘soft’ acaricides, including oxalic acid, and biopesticides such as dsRNA. In light of the widespread prevalence of acaricide resistance and an increasing varroa problem, there is an urgent need for nuanced, data-driven varroa IRM strategies.